2005
DOI: 10.1111/j.1365-2648.2005.03503.x
|View full text |Cite
|
Sign up to set email alerts
|

End of life care: a discursive analysis of specialist palliative care nursing

Abstract: Reframing the approach to specialist palliative care in the United Kingdom will require great effort on the part of all health and social care professionals, not least nurses. Critical and creative thinking are prerequisites to the development of new models of working. We suggest that a more coherent approach to research and education is required, in particular strategies that explore how patients and nurses can work together in exploring experiences of illness in order to develop more proactive approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 53 publications
(98 reference statements)
1
45
0
Order By: Relevance
“…make comparisons among studies difficult, these findings are congruent with other studies demonstrating that a range of distressing and readily identifiable problems constitute a common pathway for many individuals at the end of life [6,7,[9][10][11]. These findings thus shed empirical light on a need for healthcare systems to implement a health promotion focus on palliative care as a means to prevent problems of distress at the end of life [16]. In the context of this study, this means careful attention to symptoms and signs, with both frequent assessment and application of care modes aimed at relieving suffering and promoting subjective comfort and well-being during the end-of-life period.…”
Section: Discussionsupporting
confidence: 89%
“…make comparisons among studies difficult, these findings are congruent with other studies demonstrating that a range of distressing and readily identifiable problems constitute a common pathway for many individuals at the end of life [6,7,[9][10][11]. These findings thus shed empirical light on a need for healthcare systems to implement a health promotion focus on palliative care as a means to prevent problems of distress at the end of life [16]. In the context of this study, this means careful attention to symptoms and signs, with both frequent assessment and application of care modes aimed at relieving suffering and promoting subjective comfort and well-being during the end-of-life period.…”
Section: Discussionsupporting
confidence: 89%
“…These consequences can be either a positive or negative experience for patients. Positive experiences for patients include feeling cared for and having their needs met; [27,46] being informed [27,47-50] and being supported [27,48]. Negative experiences include pain and symptom control needs not met [51,52] not having their needs met and not being supported, [27,42,43] as wellbeing unable to manage, particular in relation to activities of daily living [10].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that home visiting nurses were able to perform their roles as effectively for clients in the terminal stage [29, 30]. Home visiting nursing service can provide clients and families not only pain management and the most suitable care to clients with unstable illness, but also mental care.…”
Section: Discussionmentioning
confidence: 99%